Cost-Effectiveness and Cost-Benefit of Cervical Cancer Screening with Liquid Based Cytology Compared with Conventional Cytology in Germany - Armstrong SF; Guest JF (Dove Medical Press, 2020)
Stephanie F Armstrong,1 Julian F Guest1,2 1Catalyst Consultants, Rickmansworth, UK; 2Faculty of Life Sciences and Medicine, King’s College, London, UKCorrespondence: Julian F GuestCatalyst Consultants, 7 Gilham Court, Ebury Road, Rickmansworth, Hertfordshire WD3 1FZ, UKTel +44 1923 450045Fax +44 1923 450046Email julian.guest@catalyst-health.comObjective: To assess the health economic impact of cervical screening with liquid based cytology (LBC) compared with conventional cytology (CC) in Germany.Methods: An economic model was constructed depicting the management of a hypothetical cohort of women aged ≥ 20 years who undergo cervical screening in Germany. The model estimated the cost-effectiveness and cost-benefit of LBC compared with CC at 2017/18 prices over a time-horizon of 70 years.Results: Performing cervical screens with LBC instead of CC is expected to increase the probability of detecting a true positive over a subject’s lifetime by 73% (0.038 versus 0.022) and of diagnosing a subject with stage 3 cervical intraepithelial neoplasia (CIN3) (0.019 versus 0.011). Women screened with LBC instead of CC are expected to have a 57% reduction in the probability of having undetected CIN3 (0.006 versus 0.014) and to experience a 44% reduction in the probability of transitioning into disease progression (from 0.018 to 0.010). The mean discounted lifetime cost of healthcare resource use associated with performing cervical screens with LBC and CC was estimated at € 4852 and € 7523 per subject respectively. For every Euro invested in cervical screening with LBC instead of CC, the German healthcare system could potentially save ∼€ 170 over a subject’s lifetime.Conclusion: Within the study’s limitations, the analysis showed that LBC affords a cost-effective cervical screening test compared with CC in Germany, since it improves detection rates and has the potential to lead to a reduction in disease progression for less cost.Keywords: cancer, cervical screening, conventional cytology, cost-effectiveness, liquid based cytology, Germany, Papanicolaou